Interaction strategies of master teachers in Indonesian vocational classroom: a case study - Akhyar Rido,; Noraini Ibrahim,; Radha M.K. Nambiar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Teachers are the foundation of a good education system and they are catalytic to nation building. In recognition of this, the Indonesian government had, in 2012, introduced a master teacher scheme under its teacher development initiatives to help identify the role model for the teaching profession. Under the initiative, teachers were selected as master teachers based on their performance in class and the learning experience they provided to their students. This study is an attempt to provide an in-depth understanding of interaction strategies, focusing on interaction management and elicitation techniques, employed by vocational English master teachers and the effects on the students. By employing conversation analysis (CA), two master teachers were selected, observed, and video recorded during formal teaching hours. Interviews were also conducted with the students to triangulate the data. The data went through a-four step analysis. The results showed that, in terms of interaction management, the teachers shared common strategies namely topic selection, topic shift, and turn taking—allocation of turn and nomination of turn taker. In addition, body language or paralinguistic featured in their communication together with code switching in English and Bahasa Indonesia. In terms of elicitation techniques, the teachers nominated individual students and asked the entire class to answer a series of openreferential and close-display questions. Besides, they posed questions repeatedly, approached students when asking questions, and posed follow up questions. The student’s reception towards the strategies was positive as they were keen to actively participate when they were given questions and opportunity to speak. The implications of this study suggest that teachers should implement such interaction management and elicitation techniques to enhance students’ participation and create learning opportunities.